The Ketogenic Diet: Safety, Morbidity, and Mortality - Nasihun, Taufiqurrachman (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2019)
In normal daily diet consisting of 52-55% carbohydrate, 32-34% fat, and 14-18% protein, a couple hours following meal and absorption there is abundant fuel supply particularly from glucose oxidation in most tissues (Kathleen M Botham and Mayes, 2015; USDA, 2015). Conversely, in ketosis condition, most tissues replace its energy requirement from glucose to ketone bodies resulting from hepatic ketogenesis (Cervenka and Kossoff, 2013; Mcdonald and Cervenka, 2017). In extra hepatic tissues, adenosine triphosphate (ATP) is synthesized through revert back of acetoacetate to acetoacetyl-CoA catalyzed by succinyl-CoA-acetoacetate CoA transferase. By this reaction acetoacetyl-CoA is split into two acetyl-CoA catalyzed by thiolase and then inserted into Krebâ€™s cycle to form ATP. Acetoacetate and b hydroxybutyrate are also able to traverse blood brain barrier and metabolized by cellular brain into ATP and used as energy also postulated as anticonvulsant (Freeman et al., 2007; J. L. Gamble et al., 1923). Moreover, when ketone bodies in circulation are increased, oxidation of ketone bodies also raised until saturation of the pathway is achieved at 12 mmol/L concentration (Kathleen M. Botham and Mayes, 2015). Concern to the energy synthesis, acetoacetate and 3-b hydroxybutyrate are the prominent ketone bodies which are readily oxidized in extra-hepatic tissues. Whilst acetone have not metabolic function and in large extent is volatilized through the lung marked by breathe odor (Kathleen M. Botham and Mayes, 2015; Paoli, 2014). Ketosis is also able to suppress hunger feeling and appetite, therefore potential to be a good regulator of the bodyâ€™s calorie intake (Dashti et al., 2004). Â However, ketosis which is induced by ketogenic diet (KD), in the long term, its safety, morbidity, and mortality remain inconclusive.